STEAM TECHNOLOGY IN TEACHING THE TOPIC” LAWS OF ABSOLUTE BLACK BODY RADIATION" (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
the laws of Absolute Black body radiation play an important role in their understanding of early data in the study of quantum mechanics. Also, mastering it will help students understand the history of the creation of quantum mechanics, basic concepts, understand their essence. This article discusses the observed effectiveness of training “laws of absolute blackbody radiation”in interdisciplinary integration in STEAM technology in students.